2016
DOI: 10.1038/srep30798
|View full text |Cite|
|
Sign up to set email alerts
|

Theophylline controllable RNAi-based genetic switches regulate expression of lncRNA TINCR and malignant phenotypes in bladder cancer cells

Abstract: TINCR is a well-known lncRNA which acts as a master regulator in somatic differentiation development. However, it is still unclear whether TINCR is also involved in caner occurrence and progression. In this study, we observed that TINCR was up-regulated in bladder cancer tissues and cells and contributed to oncogenesis and cancer progression. Silencing TINCR expression inhibited cell proliferation and promoted apoptosis in vitro, indicating that TINCR may be the potential therapeutic target for treating bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“… 8 Moreover, Zhang et al suggested that TINCR expression was obviously reduced in colorectal cancer tissues and cell lines compared with their counterparts. 15 However, there was more evidence suggesting that TINCR was overexpressed in human cancers including hepatocellular carcinoma, 16 bladder cancer, 17 breast cancer, 18 esophageal cancer 19 and gastric cancer. 20 , 21 In addition, the expression status of TINCR in lung cancer is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Moreover, Zhang et al suggested that TINCR expression was obviously reduced in colorectal cancer tissues and cell lines compared with their counterparts. 15 However, there was more evidence suggesting that TINCR was overexpressed in human cancers including hepatocellular carcinoma, 16 bladder cancer, 17 breast cancer, 18 esophageal cancer 19 and gastric cancer. 20 , 21 In addition, the expression status of TINCR in lung cancer is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…They do not encode proteins, but play important roles in regulating gene expression through both epigenetic and posttranscriptional mechanisms 6 . Although little is known about the carcinogenic mechanisms of lncRNAs, many lncRNAs have been found to be abnormally expressed in bladder cancer 7 , including UCA1 (urothelial carcinoma associated) 8 , HOTAIR (HOX transcript antisense intergenic RNA) 9 and TINCR (tissue differentiation-inducing non-protein coding RNA) 10 .Yet, the biological roles of lncRNAs in bladder cancers are largely unknown. Metastasis associated lung adenocarcinoma transcript 1(MALAT1) is a long non-coding RNA that is upregulated in many cancers, such as breast, pancreatic, lung, colon, prostate and liver cancer 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Zhang et al revealed that downregulation of TINCR promoted proliferation and metastasis in colorectal cancer and TINCR could be considered as a potential cancer suppressor gene [ 11 ]. Furthermore, Chen et al demonstrated that TINCR could promote bladder cancer development and progression and TINCR knockdown might provide a novel therapeutic strategy for bladder cancer [ 12 ].…”
Section: Discussionmentioning
confidence: 99%